2003
DOI: 10.1038/sj.bjc.6601379
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional immunotherapy of malignant effusion from colorectal cancer using the streptococcal preparation OK-432 plus Interleukin-2

Abstract: In total, 16 patients with cytologically proven malignant effusion from colorectal cancer were treated by locoregional administration of the streptococcal preparation OK-432 alone or OK-432 plus the T-cell growth factor interleukin (IL)-2, and the action mechanism of the treatment was studied. A positive clinical response, showing a cytologic disappearance of cancer cells and decrease of effusion, was observed in nine of 11 (82%) patients treated with OK-432 alone and in all five patients treated with OK-432 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Tumor cell killing by OK-DC may be particularly suitable for clinical application and development, as OK432 has been safely administered to cancer patients for many years (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cell killing by OK-DC may be particularly suitable for clinical application and development, as OK432 has been safely administered to cancer patients for many years (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…OK-432, which is a penicillin-killed and lyophilized preparation of a low-virulence strain of Streptococcus pyogenes (group A), has been successfully used as an immunotherapeutic agent against many types of malignancies, including head and neck cancer, stomach cancer, lung cancer, pancreatic cancer and colorectal cancer (Yamaguchi et al, 2003;Yoo et al, 2010;Nakamoto et al, 2011;Tano et al, 2012;Tano et al, 2013;Wada et al, 2014). It has been reported that OK-432 elicits anti-tumor effects by stimulating immunocompetent cells such as macrophages, T cells, and natural killer (NK) cells, and by inducing helper T-cell 1(Th1) type cytokines, such as IFN-γ, TNF-α, IL-6, IL-8, IL-10, IL-12, and IL-18(Oshimi et al, 1980;Saito et al, 1982;Fujimoto et al, 1997), which can augment cytotoxic T lymphocytes to antitumor.…”
Section: Introductionmentioning
confidence: 99%
“…These include inactivated bacterial superantigens from streptococcus (OK-432) or staphylococcus, which were studied in combination with other treatment modalities. Yamaguchi et al [34] combined OK-432 with IL-2 into the pleural space in 16 patients with documented MPE from colorectal cancer. There was a cytologic response and decrease in effusion volume in 9 of 11 (82%) patients treated with OK-432 alone and in all 5 patients treated with OK-432 plus IL-2.…”
Section: Ip Immunotherapymentioning
confidence: 99%